Debt maturity structure and investment decisions: Evidence of listed companies on Vietnam's stock market - Trang Van Thi Do; Thuy Duong Phan (Cogent Economics & Finance, 2022)
The article analyzes the impact of debt maturity structure and other factors on investment decisions of enterprises listed on the Vietnam's stock market from 2010 to 2019. Data used in this study are acquired from the financial statements of 558 enterprises listed on both the Ho Chi Minh and Hanoi stock exchanges in the period 2010-2019, from the FiinPro database. S-GMM regression method is utilised to analyze the influence of debt maturity structure and other factors on investment decisions of listed companies. The analysis results shows that the debt maturity structure has a positive impact on the investment decision of the enterprises. Besides, the profitability of total assets and the fixed assets turnover also have a positive impact on the investment decision of the enterprise, while liquidity and cash flow have a negative impact on investment decisions. Based on empirical results, the study proposes some recommendations to help the managers of listed companies to build a reasonable debt maturity structure in the direction of using more long-term debts to increase investment efficiency. At the same time, the study recommends some policy implications for the Government in managing macroeconomic policies in order to create favourable conditions for businesses to access many long-term capital sources.
Keywords: G30; G32; G11; 330; Debt maturity structure; investment decisions; Vietnam listed companies